Development of Wordwall-Based Assessment Instruments to Measure Higher Order Thinking Skills Science Material Temperature, Heat, and Expansion - Saputri, Anastasya Eka; Wahyuni*, Sri; Wahyuni, Diah (Jurnal Pendidikan Sains Indonesia, 2023)
The application of higher order thinking skills (HOTS) in evaluation aims to improve the quality of students' thinking, especially about the process of solving a problem. This study aims to develop a wordwall-based assessment instrument to measure HOTS. This study methods used the Borg and Gall development model with 8 stages covering, looking for potential and formulating problems, information gathering, product design, product design validation, design revision, small group trials, product revisions, field trials. Respondents who took the test were divided into 2, namely 25 students for small group trials and all of class VII SMPN 2 Maesan, Bondowoso for field trials. The questionnaires used in this study were interview questionnaires, validation questionnaires and tests to find out students' HOTS. The results showed that the validity of the assessment instrument was 80.99% with a valid category along with the items, and the reliability of the assessment instrument was 0.770. The analysis of the discriminating power of the items produced 3 items in the very good category, 10 items in the good category, 4 items in the sufficient category, and 3 items in the poor category. Then the difficulty level analysis produces 5 questions in the too easy category, 12 questions in the medium category, and 3 questions in the too difficult category. Based on the results of the research, the assessment instrument developed was stated to be valid and suitable for use for subsequent learning evaluations even though there were minor revisions